Facile synthesis of sub-monolayer Sn, Ru, and RuSn decorated Pt/C nanoparticles for formaldehyde electrooxidation - Wang, D.; Wang, J.; Lu, S.; Jiang, San Ping (Elsevier, 2014)
A novel structured catalyst for formaldehyde electrooxidation was developed by decorating sub-monolayer Sn, Ru and RuSn on the surface of Pt/C nanoparticles. The electrocatalysts were prepared by an impregnation-reduction method using H2 as the reducing agent at room temperature. The structure and electrochemical active surface area of the decorated Pt/C electrocatalysts were characterized by Xray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), energy dispersion spectroscopy (EDX) and cyclic voltammetry (CV). High electrocatalytic activities of Sn, Ru and RuSn decorated Pt/C electrodes toward formaldehyde electrooxidation in a 0.5 M H2SO4 aqueous solution were observed as compared with pure Pt/C electrode. Best results were obtained on the Sn decorated Pt/C electrocatalyst with a significantly lower onset potential and higher oxidation current in acid medium, relative to the pure Pt/C and Ru decorated Pt/C electrocatalysts. The reasons are most likely related to the fact that Sn, existed as tin oxides, has significantly higher activation and catalytic activity towards CO oxidation and the presence of Sn induces the weakly bonded CO on Pt.